Effect of pretreatment on the level of antinutritional factors in jackfruit seeds / Noor Fadilah Mohd Bakri ... [et al.] - Mohd Bakri, Noor Fadilah; Ishak, Zuwariah; Hassan, Hadijah; Mohamad, Aida; Razali, Rodhiah (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Jackfruit waste is attracting considerable widespread interest due to their good nutritious profiling. The seed of jackfruit comprises a good level of macronutrients such as dietary fiber, protein, fat as well as micronutrients like vitamins and essential acid amino. Few compounds in the seed were reported to have a beneficial role for the human health. Nevertheless, a trace level of antinutritional factors has been reported to be founded in the seeds. Tannin, phytic acid and saponin are few antinutritional factors that are regularly associated with agricultural waste. The existence of these compound in human diets may affect the overall nutritional value of the foods by averting nutrient bioavailability. The aim of this study was to investigate the effect of these two methods (germination and roasting) in minimizing the level of these antinutrients i.e. tannin and phytic acid before applying. Samples were subject to two pretreatment processes: germination and roasting. Quantifying of these two antinutritional factors was conducted via spectrophotometry method. Our results revealed that both pretreatment methods may reduce the level of tannin and phytic acid. In addition, roasted jackfruit seed contained the lowest level of tannin and phytic acid (0.1039 ±0.06 % DW and 0.0159±0.1g/100g respectively).